The molecular interplay between the gut microbiome and circadian rhythms: an integrated review - Zheng, Boyang; Wang, Liwei; Sun, Shilin; Yuan, Xingxing; Liang, Qun (Frontiers in Microbiology, 2025)
This integrated review synthesizes current evidence on the molecular interplay between the gut microbiome and circadian rhythms, emphasizing a sophisticated bidirectional communication system crucial for maintaining metabolic, immune, and neurological homeostasis. The host circadian clock orchestrates microbial composition and function through rhythmic changes in feeding-fasting cycles, hormone secretion, immune responses, and bile acid metabolism. In return, microbial metabolites, including short-chain fatty acids such as butyrate, secondary bile acids like lithocholic acid, and tryptophan derivatives, act as timing cues that influence core clock gene expression via epigenetic mechanisms, receptor-mediated signaling (GPR41/43, FXR), and neuroendocrine pathways. Disruption of this finely tuned dialogue, known as chronodisruption, often driven by modern lifestyles, predisposes individuals to a range of pathologies, including metabolic syndrome, inflammatory bowel disease (IBD), neurodegenerative disorders, and cancer. The review also evaluates promising chronotherapeutic interventions such as time-restricted eating (TRE), targeted probiotic use, and chronopharmacology, which aim to resynchronize host-microbe rhythms and restore physiological balance. Elucidating these mechanisms provides a foundational framework for developing personalized health strategies that target the gut-clock axis.